The Influence of School Principals' Transformational Leadership and Teachers' Self-Efficacy on Teacher Performance at SMP Negeri 1 Tomohon - Suiling Pontoh; Joulanda Altje Meiske Rawis; Shelty Deity Meity Sumual (International Journal of Science and Environment (IJSE), 2025)
This study aims to analyze the influence of transformational leadership of school principals and teacher self-efficacy on teacher performance at SMP Negeri 1 Tomohon. Employing a quantitative approach, data were collected through a survey involving 68 teachers using valid questionnaires. The analysis was conducted using SPSS, encompassing normality, linearity, and regression tests. The results indicate a significant influence between transformational leadership and teacher performance, with a correlation coefficient of 0.672. Teacher self-efficacy also made a positive contribution, evidenced by a significance value of 0.001 and a t-statistic of 6.107. Simultaneously, both variables explained 52.9% of the variance in teacher performance (R² = 0.529). These findings suggest that enhancing transformational leadership and teacher self-efficacy can improve the quality of education at SMP Negeri 1 Tomohon, serving as a reference for educational policymakers in formulating effective strategies.